KONTRIBUSI PEREMPUAN TERHADAP PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN DESA WISATA BATUAN GIANYAR - I Gusti Agung Febrianto (JURNAL BISNIS HOSPITALITI, 2026)
Abstract This study aims to describe women’s contributions to community empowerment in the development of Batuan Tourism Village, Gianyar, within the frameworks of community-based tourism (CBT) and hospitality. A descriptive qualitative design was employed using in-depth interviews with key informants (I1–I5) and interactive data analysis following Miles and Huberman (data reduction, display, and conclusion drawing/verification). The findings indicate that women are positioned as key actors in village tourism development, with contributions that emerge organically from everyday practices. Women’s involvement is strongly associated with household economic improvement through tourism-related activities, while their roles are flexible and multi-functional across sectors. Women also sustain the socio-cultural foundations of the destination through participation in religious activities, consumption-related tasks, and cultural preservation. In addition, women perform micro-level governance at the host–guest interface by mediating customary rules in sacred spaces, including regulating access and ensuring compliance with appropriate dress and conduct in temple areas. Reported benefits include improved service-related knowledge, strengthened community networks, and expanded employment opportunities for women. Nevertheless, participation is not evenly distributed and is constrained by women’s domestic–public double burden and scheduling conflicts with customary obligations. Institutional support from the village government and the presence of Pokdarwis provide a pathway for formalizing women’s roles to strengthen the long-term sustainability of CBT-based village tourism. Keywords: women, community empowerment, tourism village, Batuan Gianyar